#### Answer

$-385$

#### Work Step by Step

The sum of the first $n$ terms of an arithmetic sequence can be obtained by the following formula: $\frac{n(a_1+a_n)}{2},$ where $a_1$ is the first term, $a_n$ is the nth term and $n$ is the number of terms.
The nth term of an arithmetic sequence can be obtained by the following formula: $a_n=a_1+(n-1)d$, where $a_1$ is the first term and $d$ is the common difference.
Hence here: $d=-7,n=10,a_1=-7,a_{10}=-7+(10-1)(-7)=-7-63=-70$
Thus the sum:$\frac{10(-7+(-70))}{2}=5\cdot-77=-385$